Some claim for the end of Botany… but what is Botany today? - Lorenzo Peruzzi (Italian Botanist)
In times of increasing interest in plants, a major challenge lies in effectively communicating the essence of Botany: What exactly does it encompass? Who are botanists? And how do botanical gardens differ from other types of gardens? To address these questions, refined definitions that account for the blurred boundaries between the fields of Botany, Agronomy, and Medicine are proposed. By representing these three disciplines in a ternary plot, I suggest defining Botany as a biological discipline where studies have a predominant (> 50%) component of basic plant science—this area is referred to here as the ‘Triangle of Botany’. In this context, a botanist can be defined as a professional or scientist whose primary research focus is on basic research related to plant organisms. A botanical garden, therefore, is a space dedicated to the cultivation, conservation, study, and display of plants, based primarily on scientific principles grounded in basic research. The overlap between disciplines contributes to the communication difficulties in clearly defining what botanists do, especially when compared to professionals such as agronomists or doctors. The lack of distinct boundaries between these fields can lead the general public to misinterpret Botany and its practitioners. As a result, people may seek advice from “experts” who may not necessarily have a strong foundation in Botany. Similarly, botanical gardens are often perceived by the public as merely aesthetic spaces, akin to vegetable gardens or parks, rather than as scientifically-driven institutions. Disseminating refined definitions could help bridge the gap in public understanding of the role of Botany, fostering a clearer appreciation of this essential scientific field.